Nomenclatural notes and typification of Retzius names in the genus Cyperus (Cyperaceae) - Muhsina, Abdul Azeez; Maya, Chandrasekharan Nair (Phytotaxa, 2025)
The present paper discusses the typification of five names in the genus Cyperus (Cyperaceae) proposed by Retzius during 1786–1791. He described species based on the specimens, which were mainly deposited in the Lund Herbarium (LD). During the revision of South Indian Cyperus, it was found that a few names proposed by Retzius required lectotypification. In the present paper, we designate lectotypes for C. arenarius, C. cinnamomeus, C. nitens and C. setaceus. Superfluous typification of the name C. exaltatus has been corrected. We also found some overlooked duplicates (isolectotypes) for formerly designated lectotypes, and are cited accordingly.